1989
DOI: 10.1007/bf02032108
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoxanthoma elasticum and angioid streaks in two cases ofβ-thalassaemia

Abstract: Two cases of beta thalassaemia with pseudoxanthoma elasticum and angioid streaks (Grönblad-Strandberg syndrome) are reported. To the best of our knowledge, this is the first report of a combination between these two genetically determined disorders. The possible theories of the pathogenesis of pseudoxanthoma elasticum and angioid streaks are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…33 ; 37 Various studies from the early 1990s demonstrated similar ocular manifestations in β-thalassemia and PXE. 1 ; 6 ; 12 ; 15 ; 51 Aessopos and colleagues established the terms “PXE-like-lesion” and “PXE-like syndrome” to help differentiate PXE from acquired PXE-like syndrome findings. 5 PXE-like syndrome refers to the following retinal abnormalities: angioid streaks, peau d'orange, and optic disc drusen development.…”
Section: Retinal Abnormalities In β-Thalassemia Major and Intermediamentioning
confidence: 99%
“…33 ; 37 Various studies from the early 1990s demonstrated similar ocular manifestations in β-thalassemia and PXE. 1 ; 6 ; 12 ; 15 ; 51 Aessopos and colleagues established the terms “PXE-like-lesion” and “PXE-like syndrome” to help differentiate PXE from acquired PXE-like syndrome findings. 5 PXE-like syndrome refers to the following retinal abnormalities: angioid streaks, peau d'orange, and optic disc drusen development.…”
Section: Retinal Abnormalities In β-Thalassemia Major and Intermediamentioning
confidence: 99%
“…The first report of two patients affected by thalassemia and coexistent Pseudoxanthoma elasticum (PXE) was published by Aessopos and colleagues in 1989 35 . Several subsequent reports have confirmed the existence of a clinical syndrome resembling PXE in patients with thalassemia intermedia and other haemolytic conditions 36,37 …”
Section: Pseudoxanthoma Elasticummentioning
confidence: 99%
“…The first report suggesting a link between beta-thal and PXE was based on the observation that angioid streaks were actually present in both diseases (Aesopos et al, 1989). Subsequent studies confirmed that PXE-like syndrome in beta-thalassemias and SCD, although less severe, is histopathologically and clinically identical to inherited PXE consisting of indistinguishable cutaneous, ocular and vascular abnormalities due to elastic fibre calcification (BaccaraniContri et al, 2001;Bercovitch & Terry, 2004;Hamlin et al, 2003) (Figure 9).…”
Section: Genetic Conditionsmentioning
confidence: 96%